Pendampingan Persiapan ONMIPA-PT 2023 Bidang Matematika pada Materi Kombinatorik bagi Mahasiswa Universitas Fajar - Syamsuddin Mas'ud (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
The preparation assistance for Olimpiade Nasional Matematika dan IPA – Perguran Tinggi (ONMIPA-PT) 2023 in the field of mathematics is an effort to enhance the mathematical skills of students so they can compete in the competition organized by the Ministry of Education, Culture, Research, and Technology. This assistance is considered necessary because the Universitas Fajar itself does not have a specific mathematics-related program of study. The assistance provided includes giving combinatorics material to selected Universitas Fajar students. Additionally, students are given practice to sharpen their understanding of the provided material. This competition consists of three stages: the university-level selection, the regional-level selection, and the national-level selection. This activity is seen as having provided students with additional knowledge about certain combinatorics topics which they did not previously have access to at their campus, as well as an introduction to simple types of combinatorial problems that typically appear during the regional-level selection. Keywords: Assistance, Mathematics, Combinatorics, Simple.